(untitled) - Barnard, C. J. (New York, 1993)
This text provides an enjoyable introduction to quantitative biology for students in the biological sciences and explains important techniques and analytical methods in the context of the student's aim: to answer biological questions as clearly as possible. The authors introduce the various stages in the process of enquiry, starting with unstructured observation and working through to the production of a complete written report. Logical steps guide the student through each stage of the enquiry to the point where he or she will be able to carry out an open-ended project as well as cope with more structured practical work.
Phương pháp luận nghiên cứu khoa học
Keywords: Science,Biology; Methodology,Methodology